الإعجاز القرآني المتجدد = The renewable inimitability of the Quran - Shkukani, Najwa Naif; Elatrash, Radwan Jamal Yousef (Kulliyyah of Islamic Revealed Knowledge and Human Sciences (KIRKHS), International Islamic University Malaysia, 2017)
The purpose of this study is to highlight the possibility of revival the atmosphere of the miracle of the Holy Quran. And not to stop or limit it in certain aspects or an era; either by adding new ways such as scientific, numerical, psychological, and so on. Or other discoveries following the previous ways but in new dimensions; like method of reasoning miracle, which is already inserted under rhetoric miracle. And that will be looked into (by the permission of Allah) through the use of the inductive method to track the work of the scholars on it, in order to get those ways from Quranic verses, with explanation of what is intended by them, and giving example on them from the Holy Quran. In addition, the research will use the analytical approach to proof those ways, and to proof the existence of the signs and evidences for these new dimensions of Quranic miracles. In order to deduce the possibility of continuity of renewal in those dimensions, which would enrich this area of studies and open the minds and motivates them to consider, study and do more research in the Qur'an, and in other fields. Within the disciplines of Islamic doctrine and its constitution.